Drei Wege zur Unabhängigkeit : Die Dekolonisierung in Indochina, Indonesien und Malaya nach 1945 - Frey, Marc (Vierteljahrshefte für Zeitgeschichte, 2002)
This article traces the development of cultural, economic and political relations between Southeast Asia and Europe in the era of decolonization. It suggests a new approach towards the study of decolonization: instead of focusing on the political aspects, namely transfers of power, decolonization is here conceived of as a multilayered process that entailed the restructuring of economies as well as the redefinition and development of national cultures. In short, decolonization meant the creation of "imagined communities". The article looks at the period between 1945 and the mid-1960s; in particular it deals with the three principal cases of decolonization in Southeast Asia, namely Indonesia/the Netherlands, Vietnam/France, and Malaya/Great Britain. It argues that bilateral relations in the period following the transfer of power reflected the ways and means by which independence had been achieved. Former colonial powers remained actors in the region by preferentially allocating development aid to the countries concerned. Southeast Asian countries, in turn, utilized their ties to former colonial powers in order to neutralize or diffuse the influence of outside actors such as China and the United States. (Vierteljahrshefte für Zeitgeschichte / FUB)